Frequency Analysis of PWM Inverters With Dead-Time for Arbitrary Modulating Signals - Chierchie, Fernando (2014)
The effect of dead-time on the spectrum of pulsewidth modulated signals is analyzed in this paper. The study is valid for arbitrary, band-limited modulating signals, extending previous results in the literature. A simple distortion index is developed that can be used at the design stage to select dead-time or switching frequency based on maximum allowed distortion. Experimental results with various band-limited signals reveal a very good agreement between the theoretical results and the experiments.